Pengaruh Konten Marketing dan Review Produk terhadap Keputusan Pembelian - Amelia Khoerunnisa; Dede R. Oktini; Mochamad Malik Akbar Rohandi (UNISBA Press, 2024)
Abstract. The culinary industry continues to experience changes thanks to innovation from human creative ideas in creating new variations of food and drinks. Bandung Makuta Cake is a successful example of utilizing creativity and innovation to create unique and attractive products. To remain competitive in the culinary industry, Bandung Makuta Cake uses TikTok social media as a platform to promote their products through marketing content and product reviews, to attract the attention of potential consumers. This research aims to test and find out how marketing content and product reviews affect Bandung Makuta cake purchasing decisions among Bandung City consumers, as well as to determine the influence of marketing content and product reviews on purchasing decisions. This research is included in the quantitative method. The object of this research is the TikTok user community who live in the city of Bandung and have made purchases or shopped in Bandung Makuta with a total of 110 respondents who were narrowed down again based on sampling criteria to 100 respondents. The data analysis used is descriptive and verification analysis, namely by using multiple linear regression analysis, T test, F test, and coefficient of determination. The results of this research show that marketing content partially has a positive effect on purchasing decisions, product reviews have a positive effect on purchasing decisions. Then simultaneously marketing content and product reviews have a positive influence on purchasing decisions. Abstrak. Industri kuliner terus mengalami perubahan berkat inovasi dari ide-ide kreatif manusia dalam menciptakan variasi baru makanan dan minuman. Bandung Makuta Cake merupakan contoh sukses dalam memanfaatkan kreativitas dan inovasi untuk menciptakan produk yang unik dan menarik. Untuk tetap kompetitif di industri kuliner, Bandung Makuta Cake memanfaatkan media sosial TikTok sebagai platform untuk mempromosikan produk mereka melalui konten marketing dan review produk, guna menarik perhatian calon konsumen. Penelitian ini bertujuan untuk menguji dan mengetahui bagaimana gambaran konten marketing, review produk terhadap keputusan pembelian Bandung Makuta cake pada Konsumen Kota Bandung, serta untuk mengetahui pengaruh konten marketing, review produk terhadap keputusan pembelian. Penelitian ini termasuk ke dalam metode kuantitatif. Objek pada penelitian ini adalah masyarakat pengguna Tiktok yang berdomisili di Kota Bandung dan pernah melakukan pembelian atau belanja di Bandung Makuta dengan jumlah 110 responden yang dikerucutkan kembali berdasarkan kriteria sampling menjadi 100 responden. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif yaitu dengan menggunakan analisis regresi linier berganda, uji T, uji F, dan koefisien determinasi. Hasil penelitian ini menunjukkan bahwa konten marketing secara parsial berpengaruh positif terhadap keputusan pembelian, review produk berpengaruh positif terhadap keputusan pembelian. Lalu secara simultan konten marketing dan review produk berpengaruh positif terhadap keputusan pembelian.